Prevalence of Amiodarone-Induced Thyrotoxicosis and Associated Risk Factors in Japanese Patients - Toyoyoshi Uchida; Takatoshi Kasai; Atsutoshi Takagi; Gaku Sekita; Koji Komiya; Kageumi Takeno; Nayumi Shigihara; Kazunori Shimada; Katsumi Miyauchi; Yoshio Fujitani; Hiroyuki Daida; Hirotaka Watada (International Journal of Endocrinology)
Amiodarone is a widely used agent for life-threatening arrhythmias. Although amiodarone-induced thyrotoxicosis (AIT) is a major adverse effect that can cause recurrence of arrhythmias and exacerbation of heart failure, risk factors for AIT among amiodarone-treated Japanese patients have not been elucidated. Here, we investigated the prevalence and predictive factors for AIT. The study subjects were 225 patients treated with amiodarone between 2008 and 2012, who were euthyroid before amiodarone therapy. All patients with AIT were diagnosed by measurement of thyroid hormones and ultrasonography. Among the 225 subjects, 13 patients (5.8%) developed AIT and all the patients were classified as Type 2 AIT. Baseline features of patients with AIT were not different from those who did not develop AIT, except for age (AIT, 55.1 ± 13.8, non-AIT, 68.1 ± 12.0 years, P<0.001). Multivariate analyses using the Cox proportional hazard model identified age as the sole determinant of AIT (hazard ratio: 0.927, 95% confidence interval: 0.891–0.964). Receiver operating characteristic curve analysis identified age of 63.5 years as the cutoff value for AIT with sensitivity of 70.3% and specificity of 69.2%. In summary, this study showed that the prevalence of AIT is 5.8% in Japanese patients treated with amiodarone and that young age is a risk factor for AIT.